Integrated Port Traffic Management using Automatic Identification System and Radar - Amran, Nur Aireen; Koto, Jaswar (International Society of Ocean, Mechanical and Aerospace -scientists and engineers- (ISOMAse), 2016)
In Vessel Traffic System (VTS), AIS can detect a larger number of targets without considering the shadow effect and can provide more voyage information for port center. For radar system can detect target actively even buoys or rock no matter ship size or fitted equipment. But even radar can detect all targets, it is cannot give full information as AIS. AIS can give full information such as types of ship, size, name, MMSI number and etc. AIS and radar system is very important in the VTS to control ship in and out at the port area. They have to use two different computers, which is one computer for AIS and another computer is for radar systems. By integrating AIS and radar, the officer can control port with more accurate and systematic. This paper will focus on integration of AIS and Radar for managing the movement of vessels in port for safety purpose by taking Port TanjungPelepas (PTP) as a case study.